1994
DOI: 10.1007/bf02007765
|View full text |Cite
|
Sign up to set email alerts
|

Investigations with the selective PKC inhibitor chelerythrine on human basophils

Abstract: Modulation of protein kinase C (PKC) activity in basophils (B) can influence IgE-mediated histamine release (HR). The present study investigated the effects of chelerythrine, which inhibits isolated PKC (IC50 0.7 microM), on different activation pathways in B. Fc epsilon RI-mediated HR was strongly inhibited by chelerythrine (86.5 +/- 5.4%, 5 microM, n = 11). TPA-induced mediator release was also suppressed: 77.1 +/- 8.5% inhibition (7.5 microM). HR due to non-immunological stimuli (A23187, FMLP) was strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…For example, rat liver alanine aminotransferase is inhibited by adduct formation between thiol groups of the enzyme and the iminium bond of chelerythrine (16). Chelerythrine also inhibits taxol-mediated polymerization of rat brain tubulin (32), histone kinase activity using partially purified PKC from the rat lacrimal gland (33), pyrogen-induced expression of tissue factor in endothelial cells, histamine release induced by aggregation of IgE-receptor on human basophils (34,35), Na ϩ ,K ϩ ,2Cl Ϫ cotransporter in Ehrlich mouse ascites tumor cells (36), and invasion of metastatic human follicular thyroid cancer (37). We have recently found that angoline and chelerythrine inhibit 7,12-dimethylbenz(a)anthracene-induced preneoplastic lesion formation in mouse mammary gland organ culture by approximately 60% at a test concentration of 10 M (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rat liver alanine aminotransferase is inhibited by adduct formation between thiol groups of the enzyme and the iminium bond of chelerythrine (16). Chelerythrine also inhibits taxol-mediated polymerization of rat brain tubulin (32), histone kinase activity using partially purified PKC from the rat lacrimal gland (33), pyrogen-induced expression of tissue factor in endothelial cells, histamine release induced by aggregation of IgE-receptor on human basophils (34,35), Na ϩ ,K ϩ ,2Cl Ϫ cotransporter in Ehrlich mouse ascites tumor cells (36), and invasion of metastatic human follicular thyroid cancer (37). We have recently found that angoline and chelerythrine inhibit 7,12-dimethylbenz(a)anthracene-induced preneoplastic lesion formation in mouse mammary gland organ culture by approximately 60% at a test concentration of 10 M (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of JNK and p38 is mediated by upstream kinases, MEKK1 and MKK4, and regulates apoptosis. Chelerythrine is known to display a variety of biological activities, such as inhibition of taxol-mediated polymerization of rat brain tubulin (47) and histamine release induced by aggregation of the IgE receptors on human basophils (34). Chelerythrine is also shown to stimulate protein phosphorylation in the mitochondrial fraction of rat retina (35).…”
Section: Dominant-negative Mutants Of Mekk1 Mkk4 Jnk1 and P38 Blocmentioning
confidence: 99%
“…The possibility must be considered that presently unknown kinases may be the targets responsible for the results obtained in this study. For example, chelerythrine is currently claimed to be selective for PKC (Herbert et al, 1990), but the nature of its inhibition, which is via the catalytic domain which is homologous with other protein kinases (Von Stebut et al, 1994) may render it potentially less selective. Indeed, chelerythrine has been observed to have a paradoxical stimulatory effect on the phosphorylation of a 20 kDa protein (Lombardini, 1995).…”
Section: Discussionmentioning
confidence: 99%